Local administration of Tiludronic Acid downregulates important mediators involved in periodontal tissue destruction in experimental periodontitis in rats - Furlaneto, Flávia A.C.; Nunes, Nara L.T.; Souza, Ricardo B.; Yamamoto, Kely O.; Oliveira Filho, Ivan Lima; Frota, Nicolly P.R.; Chaves, Hellíada; Lisboa, Mario; Taba Jr., Mario; Ervolino, Edilson [UNESP]; Messora, Michel R. (Elsevier, 2018)
Objective The purpose of this study was to evaluate whether local administration of TIL could influence the expression of the inflammatory mediators IL-1β, TNF-α, MMP-8 and COX-2 in rats with experimental periodontitis (EP). Methods Twenty-four adult male rats (Rattus norvegicus, albinus, Wistar) were assigned to groups C, EP, EP-TIL (C–Control group, EP–Periodontitis groups). On EP groups, a ligature was placed around maxillary 2nd molars on day 1. On group EP-TIL, 20 μL of TIL solution (1 mg/kg body weight) was injected into the subperiosteal palatal area adjacent to the maxillary 2nd molar every other day until euthanasia (day 11). Alveolar bone loss was morphometrically analyzed. mRNA expressions of IL-1β, TNF-α, MMP-8 and COX-2 were assessed by qPCR. IL-1β, TNF-α, MMP-8 and COX-2 were immunohistochemically analyzed. Data were analyzed statistically. Results Group EP-TIL presented reduced alveolar bone loss when compared with group EP (p < 0.05). Group EP-TIL presented decreased mRNA expressions of IL-1β, TNF-α, MMP-8 and COX-2 and reduced immunolabeling of IL-1β, TNF-α and MMP-8 when compared with group EP (p < 0.05). No differences regarding the immunolabeling of COX-2 were found when group EP-TIL was compared with the other groups (p > 0.05). Conclusion Within the limits of this study, it can be concluded that local administration of TIL downregulates important mediators involved in periodontal tissue destruction in ligature-induced periodontitis in rats.
Keywords: Bisphosphonates; Bone; Inflammation; Periodontal disease